Club cell protein (CC16) in plasma, bronchial brushes, BAL and urine following an inhaled allergen challenge in allergic asthmatics. (2nd January 2018) - Stenberg, Henning; Wadelius, Erik; Moitra, Subhabrata; Åberg, Ida; Ankerst, Jaro; Diamant, Zuzana; Bjermer, Leif; Tufvesson, Ellen
Abstract: Background: Club cell protein (CC16) is a pneumoprotein secreted by epithelial club cells. CC16 possesses anti-inflammatory properties and is a potential biomarker for airway epithelial damage. We studied the effect of inhaled allergen on pulmonary and systemic CC16 levels. Methods: Thirty-four subjects with allergic asthma underwent an inhaled allergen challenge. Bronchoscopy with bronchoalveolar lavage (BAL) and brushings was performed before and 24 h after the challenge. CC16 was quantified in BAL and CC16 positive cells and CC16 mRNA in bronchial brushings. CC16 was measured in plasma and urine before and repeatedly after the challenge. Thirty subjects performed a mannitol inhalation challenge prior to the allergen challenge. Results: Compared to baseline, CC16 in plasma was significantly increased in all subjects 0–1 h after the allergen challenge, while CC16 in BAL was only increased in subjects without a late allergic response. Levels of CC16 in plasma and in the alveolar fraction of BAL correlated significantly after the challenge. There was no increase in urinary levels of CC16 post-challenge. Mannitol responsiveness was greater in subjects with lower baseline levels of CC16 in plasma. Conclusions: The increase in plasma CC16 following inhaled allergen supports the notion of CC16 as a biomarker of epithelial dysfunction.